Increase Natural Serotonin Hormone with Pranayama Ante-Natal Yoga Method to Control Anxiety in Pregnant Women - Nicky Danur Jayanti; Senditya Indah Mayasari (Jurnal Kebidanan, 2023)
The anxiety of pregnant women can be caused because the fear and fear that most pregnant women feel is anxiety and fear in facing childbirth. Anxiety will have a negative impact on pregnant women from pregnancy to delivery. The hormone serotonin as a mental health hormone that can prevent anxiety, mood, or depression can be produced by the body naturally. Some ways that you can increase the release of the hormone serotonin naturally are by exercising, massage, sunbathing in the sun, and meditation or yoga. Analyzing the increase in natural serotonin hormones with the pranayama antenatal yoga method to control anxiety in pregnant women. This research is quasi-experimental research, with a nonrandomized pretest-post-test control group design. The population in this study were pregnant women in the PMB "C" area. The number of samples was 20 pregnant women who were given yoga exercise treatment and 20 pregnant women as the control group. Statistical test using paired t-test. The results showed that yoga was significantly effective in overcoming maternal anxiety, the p-value showed 0.019 (p <0.05), and the positive t-value indicated that yoga had a good impact on overcoming the anxiety of pregnant women. Yoga practice during pregnancy helps reduce anxiety, increase self-confidence in coping with childbirth and reduce physical complaints and prevent the increase in symptomatological symptoms, and has a statistically significant effect on anxiety levels. The results showed that yoga was significantly effective in overcoming maternal anxiety, the p-value showed 0.019 (p <0.05), and the positive t-value indicated that yoga had a good impact on overcoming the anxiety of pregnant women. Yoga practice during pregnancy helps reduce anxiety, increase self-confidence in coping with childbirth and reduce physical complaints and prevent the increase in symptomatological symptoms, and has a statistically significant effect on anxiety levels. The results showed that yoga was significantly effective in overcoming maternal anxiety, the p-value showed 0.019 (p <0.05), and the positive t-value indicated that yoga had a good impact on overcoming anxiety of pregnant women. Yoga practice during pregnancy helps reduce anxiety, increase self-confidence in coping with childbirth and reduce physical complaints and prevent the increase in symptomatological symptoms and has a statistically significant effect on anxiety levels.